2015
DOI: 10.5006/1633
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Modeling Studies for Sediment Deposition as Sites for Under-Deposit Corrosion in Oil Transmission Pipelines

Abstract: Transmission heavy crude oil carries water-wetted solid particles. Studies have shown that these particles can accumulate on the pipe floor and cause under-deposit corrosion and that the incidence of accumulation is strongly correlated to locations downstream of overbends. Computational fluid dynamics (CFD) analysis of light and heavy crude oil flows in a representative segment of a real transmission pipeline suggested that the deposition patterns in heavy oil flow are a result of low near-wall velocity, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although studies have been conducted to understand how deposits form in order to mitigate deposit formation [1][2] and to experiment with inhibitor packages to understand the risk and mechanisms involved with inhibition of UDC, 3,7-10 no formal attempt has been made to observe the effects of specific chemical components in an inhibitor package on UDC. The objective of this study was to test individual chemical components used in industrial inhibitor packages against localized UDC.…”
Section: -Mercaptoethanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have been conducted to understand how deposits form in order to mitigate deposit formation [1][2] and to experiment with inhibitor packages to understand the risk and mechanisms involved with inhibition of UDC, 3,7-10 no formal attempt has been made to observe the effects of specific chemical components in an inhibitor package on UDC. The objective of this study was to test individual chemical components used in industrial inhibitor packages against localized UDC.…”
Section: -Mercaptoethanolmentioning
confidence: 99%
“…Under deposit corrosion (UDC) is a localized corrosion that occurs where sediments, carried through a production or transmission pipeline, have settled in stagnant or low-flow sections of a pipeline and mitigation strategies are ineffective or impractical. Computational fluid dynamics studies [1][2] have recently been conducted to understand mechanisms of solids deposition in order to mitigate deposit formation. Conclusions from these studies confirmed specific conditions related to flow and pipeline geometry reduce the near-wall velocity at the pipe floor, allowing deposits containing a mixture of water, hydrocarbons, microorganisms, and inorganic compounds to form.…”
Section: Introductionmentioning
confidence: 99%